Produksi Program Acara Pro 2 Activity di Pro 2 RRI Semarang (Editor) - Kristiawan Agma Bima Setyanto; Lintang Ratri Rahmiaji (Interaksi Online, 2020)
Radio media that can be said by friends of the public from various walks of life as media can accompany, entertain, and convey a variety of new information needed by the community. Radio is said to be a friend of the people from various walks of life because radio can be used from a variety of people with different educational backgrounds and customs to consume radio that provides information through voice networks. LPP RRI was established on September 11, 1945 and on that date was made the day of the RRI (Radio Republik Indonesia) which is commemorated every year. RRI Semarang is one part of the national radio in Indonesia that always carries out various creativities. RRI has four programs, one of which is specifically for young people, namely Pro 2 RRI. The author is in charge as an editor whose job is to prepare all creative content from earcather, radio show (paparazy), viral interlude (selvi), and voxpop. In addition, the editor also made pamphlets that would later be used to conduct buzzing activities through the official social media Pro 2 RRI Semarang such as Instagram, WhatsApp, Facebook and Twitter which were carried out while the broadcast was in progress. Pro 2 RRI Semarang has a program called Pro 2 Activity which broadcasts every day for three hours from 06.00 - 09.00 WIB. The reason for choosing this program to be developed is because of the lack of enthusiasm of listeners towards the Pro 2 Activity program. Seen from the lack of response on social media listeners. After the program was run for 8 weeks using a new concept the editor and the team succeeded in producing 24 episodes and the Pro 2 Activity program experienced an increase in listeners from initially 3 to 4 listeners every day to 8 to 10 listeners. And if in the future there are still field works in Pro 2 RRI Semarang is expected to provide better breakthroughs to increase listeners